Selling our youth : graduate stories of class, gender and work in challenging times - Bradley, Harriet; Waller, Richard; Bentley, Laura (Bingley, U.K. : Emerald Publishing Limited, 2022)
Selling Our Youth explores how the class origins of recent graduates continue to shape their labour market careers and thus reproduce class privilege and class disadvantage. It shows how class and gender combine to influence these young adults' opportunities and choices, in an era when this generation has been characterized as the first likely to end up worse off economically than their parents. The authors draw upon the landmark Paired Peers research project - an empirical longitudinal study of recent graduates in England - to explore their experiences of the contemporary globalized labour market. It demonstrates how many of these young, well qualified adults struggle to achieve stable and rewarding employment in the context of the overstocked graduate supply, precarious work and exploitative working conditions. Government policies of austerity, which were in place when these young people graduated in 2013, meant this generation faced the challenges of a lower wage economy and a housing crisis. The subsequent arrival of Covid-19 and its disastrous impacts on the local and global economy are making these challenges even tougher. The authors further explore the way differences of class and gender impact upon graduate trajectories.
Introduction -- Chapter 1. Young Graduates' Employment Trajectories in Context -- Chapter 2. The Paired Peers Project and its Findings -- Chapter 3. Reaching for the Top: Middle-Class Men's Work Stories -- Chapter 4. Slow Train to the Top? Middle-class Women's Narratives of Building a Career -- Chapter 5. Making their Way: Working-Class Men's Work Stories -- Chapter 6. Confronting Double Disadvantage: Working-class Women -- Chapter 7. Conclusions.
Includes bibliographical references and index.
Keywords: College graduates -- Employment -- Great Britain; Social classes -- Great Britain; Labor market -- Social aspects -- Great Britain; Business & Economics, Careers -- General; Employment & unemployment